Transformation of Regional Public Service Agencies in Improving Performance Al Ihsan Hospital, West Java Province - Yusuf Habibie, Ahmad; Firman Sampurna, Agung (Pelopor Publikasi Akademika, 2024)
This research was conducted to analyze the performance of governance in implementing BLUD and provide recommendations for financial governance at Al Ihsan Hospital, West Java Province. This research uses a post-positivism paradigm using a balanced scorecard (BSC) approach using primary data and secondary data obtained from interviews and documentation studies. The analytical tools used are for financial performance including financial ratios and operational cost ratios to operational income (BOPO) as well as compliance aspects of financial management. Meanwhile, service performance includes customer aspects, internal business processes and learning and growth aspects. So, this research will depict the transformation conditions of BLUD management in the field in terms of financial and service performance aspects. The research results show that the growth and learning perspective has the best value compared to the other four perspectives. Therefore, in order for RSUD's to be able to implement better BLUD governance so that they can improve performance, this can be done through adjustments to regional regulations to accommodate the flexibility needs of BLUD's and implementation conditions that continue to develop in the field.